Safety and immunogenicity of a two-dose heterologous Ad26.ZEBOV and MVA-BN-Filo Ebola vaccine regimen in adults in Europe (EBOVAC2): a randomised, observer-blind, participant-blind, placebo-controlled, phase 2 trial. Issue 4 (April 2021) - Pollard, Andrew J; Launay, Odile; Lelievre, Jean-Daniel; Lacabaratz, Christine; Grande, Sophie; Goldstein, Neil; Robinson, Cynthia; Gaddah, Auguste; Bockstal, Viki; Wiedemann, Aurelie; Leyssen, Maarten; Luhn, Kerstin; et al.
Summary: Background: To address the unmet medical need for an effective prophylactic vaccine against Ebola virus we assessed the safety and immunogenicity of three different two-dose heterologous vaccination regimens with a replication-deficient adenovirus type 26 vector-based vaccine (Ad26.ZEBOV), expressing Zaire Ebola virus glycoprotein, and a non-replicating, recombinant, modified vaccinia Ankara (MVA) vector-based vaccine, encoding glycoproteins from Zaire Ebola virus, Sudan virus, and Marburg virus, and nucleoprotein from the Tai Forest virus. Methods: This randomised, observer-blind, placebo-controlled, phase 2 trial was done at seven hospitals in France and two research centres in the UK. Healthy adults (aged 18–65 years) with no history of Ebola vaccination were enrolled into four cohorts. Participants in cohorts I–III were randomly assigned (1:1:1) using computer-generated randomisation codes into three parallel groups (randomisation for cohorts II and III was stratified by country and age), in which participants were to receive an intramuscular injection of Ad26.ZEBOV on day 1, followed by intramuscular injection of MVA-BN-Filo at either 28 days (28-day interval group), 56 days (56-day interval group), or 84 days (84-day interval group) after the first vaccine. Within these three groups, participants in cohort II (14:1) and cohort III (10:3) were further randomly assigned to receive either Ad26.ZEBOV or placebo on day 1, followed by either MVA-BN-Filo or placebo on days 28, 56, or 84. Participants in cohort IV were randomly assigned (5:1) to receive one dose of either Ad26.ZEBOV or placebo on day 1 for vector shedding assessments. For cohorts II and III, study site personnel, sponsor personnel, and participants were masked to vaccine allocation until all participants in these cohorts had completed the post-MVA-BN-Filo vaccination visit at 6 months or had discontinued the trial, whereas cohort I was open-label. For cohort IV, study site personnel and participants were masked to vaccine allocation until all participants in this cohort had completed the post-vaccination visit at 28 days or had discontinued the trial. The primary outcome, analysed in all participants who had received at least one dose of vaccine or placebo (full analysis set), was the safety and tolerability of the three vaccination regimens, as assessed by participant-reported solicited local and systemic adverse events within 7 days of receiving both vaccines, unsolicited adverse events within 42 days of receiving the MVA-BN-Filo vaccine, and serious adverse events over 365 days of follow-up. The secondary outcome was humoral immunogenicity, as measured by the concentration of Ebola virus glycoprotein-binding antibodies at 21 days after receiving the MVA-BN-Filo vaccine. The secondary outcome was assessed in the per-protocol analysis set. This study is registered at ClinicalTrials.gov, NCT02416453, and EudraCT, 2015-000596-27. Findings: Between June 23, 2015, and April 27, 2016, 423 participants were enrolled: 408 in cohorts I–III were randomly assigned to the 28-day interval group (123 to receive Ad26.ZEBOV and MVA-BN-Filo, and 13 to receive placebo), the 56-day interval group (124 to receive Ad26.ZEBOV and MVA-BN-Filo, and 13 to receive placebo), and the 84-day interval group (117 to receive Ad26.ZEBOV and MVA-BN-Filo, and 18 to receive placebo), and 15 participants in cohort IV were assigned to receive Ad26.ZEBOV and MVA-BN-Filo (n=13) or to receive placebo (n=2). 421 (99·5%) participants received at least one dose of vaccine or placebo. The trial was temporarily suspended after two serious neurological adverse events were reported, one of which was considered as possibly related to vaccination, and per-protocol vaccination was disrupted for some participants. Vaccinations were generally well tolerated. Mild or moderate local adverse events (mostly pain) were reported after 206 (62%) of 332 Ad26.ZEBOV vaccinations, 136 (58%) of 236 MVA-BN-Filo vaccinations, and 11 (15%) of 72 placebo injections. Systemic adverse events were reported after 255 (77%) Ad26.ZEBOV vaccinations, 116 (49%) MVA-BN-Filo vaccinations, and 33 (46%) placebo injections, and included mostly mild or moderate fatigue, headache, or myalgia. Unsolicited adverse events occurred after 115 (35%) of 332 Ad26.ZEBOV vaccinations, 81 (34%) of 236 MVA-BN-Filo vaccinations, and 24 (33%) of 72 placebo injections. At 21 days after receiving the MVA-BN-Filo vaccine, geometric mean concentrations of Ebola virus glycoprotein-binding antibodies were 4627 ELISA units (EU)/mL (95% CI 3649–5867) in the 28-day interval group, 10 131 EU/mL (8554–11 999) in the 56-day interval group, and 11 312 mL (9072–14106) in the 84-day interval group, with antibody concentrations persisting at 1149–1205 EU/mL up to day 365. Interpretation: The two-dose heterologous regimen with Ad26.ZEBOV and MVA-BN-Filo was safe, well tolerated, and immunogenic, with humoral and cellular immune responses persisting for 1 year after vaccination. Taken together, these data support the intended prophylactic indication for the vaccine regimen. Funding: Innovative Medicines Initiative and Janssen Vaccines & Prevention BV. Translation: For the French translation of the abstract see Supplementary Materials section.